Geochemical signature and reservoir conditions of Early Jurassic calc-alkaline volcanic rocks from Lonco Trapial Formation, Central Patagonia - Zaffarana, Claudia Beatriz (2018)
Central Patagonia is traversed by a belt of Early to Middle Jurassic calc-alkaline intermediate volcanic rocks interspersed with more felsic volcanic rocks which are associated with the widespread magmatism that took place during Gondwana break-up times. This work uses K–Ar and Ar–Ar dating and whole-rock and phenocryst (plagioclase, amphibole, clinopyroxene and titanomagnetite) compositional data to refine the age, geochemical signature and reservoir conditions of these volcanic rocks, which are known as Lonco Trapial Formation. The andesites, dacites and trachydacites which were the object of this study have either amphibole or clinopyroxene as the main mafic phenocryst (amphibole-bearing and clinopyroxene-bearing volcanic rocks, respectively), though amphibole is the main mafic phase. Despite the calc-alkaline signature a mild alkaline affinity emerges from some whole-rock trace elements content and from mineral chemistry (amphibole, clinopyroxene and titanomagnetite compositions). The magmatic evolution of the Lonco Trapial andesites, dacites and trachydacites was governed by fractionation of amphibole, clinopyroxene, plagioclase, titanite, titanomagnetite and apatite. Amphibole phenocrysts show an overall normal chemical zoning. The cores of the amphiboles crystallized over a temperature range of 869–916 °C, whereas the rims crystallized over a temperature range of 826–867 °C. Shallow to intermediate depths (2–8 kbar, ∼7–26 km) were inferred from geobarometric calculations. Crystallization temperatures are slightly higher in the clinopyroxene-bearing volcanic rocks, consistent with their more primitive character. The geobarometric estimations of this work are coherent with the lack of marine ingressions and with geophysical estimations which suggest that the Early Jurassic Moho depth would have been ≥35 km The combination of whole-rock and mineral geochemistry is consistent with an extensional affinity for this paleo-volcanic belt.